A Study of Career Ladder Competencies of Nurses in Burn Unit, Tertiary Hospitals - Manjit, Sasipimon; Prachusilpa, Gunyadar; Buachu, Thinnakorn (Journal of health and health management, 2026)
This descriptive research aimed to establish career ladder competencies for nurses working in the burn unit of a tertiary care hospital. A three-round Delphi technique was employed, involving a panel of 20 experts in burn nursing and care. The study was conducted in three phases: (1) expert interviews to identify essential competencies; (2) development of a rating-scale questionnaire based on content analysis of the interviews; and (3) consensus-building through statistical analysis using medians and interquartile ranges, followed by expert re-evaluation for final validation. Research instruments included an interview guide and the Delphi questionnaire. Qualitative data were analyzed using content analysis, while quantitative data were analyzed using median and interquartile range. The study identified nine core competency domains for burn unit nurses: 1) Critical burn nursing care; 2) Infection and complication control; 3) Burn wound management; 4) Pain management; 5) Physical and psychosocial rehabilitation; 6) Nutritional management; 7) Discharge planning and end-of-life care; 8) Interdisciplinary communication and teamwork; and 9) Advanced technology and medical equipment utilization. While these core domains apply to all levels, proficiency levels vary across the career ladder: 1) Novice: Performs basic nursing care under professional supervision; 2) Advanced Beginner: Demonstrates capability in care planning and collaborative teamwork; 3) Competent: Collaborative care planning and utilization of evidence-based practice; 4) Proficient: Focuses on comprehensive, holistic nursing care and clinical judgment; and 5) Expert: Emphasizes team development and innovation.